Effects of Partial Replacement of Si by Al on Cold Formability in Two Groups of Low-Carbon Third-Generation Advanced High-Strength Steel Sheet: A Review - Koh-ichi Sugimoto (Metals, 2022)
Partial replacement of Si by Al improves the coatability (or galvanizing property) of Si-Mn advanced high-strength steel (AHSS) sheets. In this paper, the effects of the partial replacement on the microstructure, tensile property, and cold formability are reported for the low-carbon third-generation AHSS sheets, which are classified into two groups, “Group I” and “Group II”. The partial replacement by 1.2 mass% Al increases the carbon concentration or mechanical stability of retained austenite and decreases its volume fraction in the AHSSs, compared to Al-free AHSSs. The partial replacement deteriorates the tensile ductility and stretch formability in the AHSSs with a tensile strength above 1.2 GPa. On the other hand, it achieves the same excellent stretch-flangeability as Al-free AHSSs. A complex addition of Al and Nb/Mo further enhances the stretch-flangeability. The cold formabilities are related to the heat treatment condition and microstructural and tensile properties, and the stress state.